Application of Goat Manure and Agriculture Lime in Biopori Infiltration Holes (BIH) on Soil CEC, Soil Exchangeable-K and Fresh Coffee Cherry Yield - Ifadah, Nisfi Fariatul; Ramadhani, Muhammad Hibatullah; Alfathin, Syifa Chairani; Soemarno, Soemarno (Journal of Coffee and Sustainability, 2025)
Coffee plants (Coffea sp.) are a plantation commodity that is widely cultivated in Malang Regency, East Java. This plant has high economic value and is a source of income for coffee farmers. The productivity of smallholder coffee plantations smallholder's in Malang Regency, East Java, is experiencing a downward trend, including smallholder coffee plantations in the Wajak sub-district. This is related to the condition of the sandy soil at the coffee plantation location, this sandy soil usually experiences drought in the long dry season, is sensitive to erosion and leaching of nutrients, and has a low level of soil fertility. The use of manure and lime in biopore infiltration holes (BIH) is considered to be a solution to overcome soil fertility problems in coffee plantations in Wajak Sub-District, Malang Regency. Field experiments were carried out to analyze the effects of manure and lime in BIH on soil chemical properties (Soil CEC and Exch-K) and coffee cherry yield. The experimental treatments are PO (Control), BK (Empty BIH: Biopore Infiltration Hole), KK (BIH + Goat manure 10 ton. ha-1), KP (BIH + Agriculture-lime 4.9 ton. ha-1), KKP (BIH + Goat manure 10 ton. ha-1 + Ag-lime 4.9 ton. ha-1). Each of these treatments is replicated five times in a Randomized Block Design (RBD).  Results of this research show that the combination of 10 tons. ha-1 of goat manure and 4.9 tons. ha-1 of agricultural lime added into the BIH increases the cation exchange capacity (soil CEC) by 22% and the soil exch-K content by 49.23% compared to the control treatment, and it increase coffee cherry yield significantly.